Geographic overlaps between priority areas for forest carbon storage efforts and those for delivering peacebuilding programs: implications for policy design - Castro Nuñez, Augusto; Mertz, Ole; Sosa, Chrystian C. (IOP Publishing, 2017)
Of the countries considering national-level policies for incentivizing reductions in forest-based greenhouse gas emissions (REDD+), some 25 are experiencing (or are emerging from) armed-conflicts. It has been hypothesized that the outcomes of the interactions between carbon-storage and peacebuilding efforts could result in either improved or worsened forest conservation and likewise increased or decreased conflict. Hence, for this study we explore potential interactions between forest carbon-storage and peacebuilding efforts, with Colombia as a case study. Spatial associations between biomass carbon and three conflict-related variables suggest that such interactions may exist. Nonetheless, while priority areas for carbon-focused conservation are presumably those at highest risks of deforestation, our research indicates that forests with lower risk of deforestation are typically those affected by armed-conflict. Our findings moreover highlight three possible roles played by Colombian forested municipalities in armed groups' military strategies: venues for battle, hideouts, and sources of natural resources to finance war.